Clinical and Laboratory Markers of Acute Dengue Infection - Mujeeb ur Rahman; Shahneela Tabassum; Muhammad Salman; Rana Shahid Hafeez; Ausaf Khan; M Nasir Khoso; Kanwal Sartaj (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: To determine frequency of clinical and laboratory markers in the early stage of dengue infection. Methods: From July 13, 2023 to October 12, 2023, this descriptive cross-sectional study was carried out in the department of Medicine at PNS RAHAT Hospital, Karachi. Subjects were enrolled in accordance with eligibility criteria and informed verbal and written consent were taken. A physical examination, clinical history, demographic information, and pertinent baseline investigations were completed. Clinical markers were recorded during the course of illness and endorsed in proforma. All patients were laboratory evaluated for dengue NS-1 antigen and IgM by ELISA method. For data analysis, SPSS software, version 20, was utilized. Results: A total number of 106 patients were recruited. When clinical markers of acute dengue infection were assessed, 40 (37.9%) had vomiting, 49 (46.5%) had Myalgia and 44 (41.75%) had Petechiae. When laboratory markers of acute dengue infection were assessed, 92 (87%) had Leucopenia, 89 (84%) had Thrombocytopenia and 94 (88.9%) had AST/ALT > 1.5. Conclusion: Clinicians still face difficulties in diagnosing dengue infection in its early stages so this study findings may help in establishing early diagnosis and can help clinicians to make rational clinical decisions during evaluation of a patient with suspected DF in resource-poor setups, where facility of detection of serum NS1 antigen is not available.